Calculation method on the minimum inserted depth of rigid anti-slide piles in the stable layer with oblique top surfaces in the downslope area - Shiguo XIAO; Yuan QI; Laibin SUN (Zhongguo dizhi zaihai yu fangzhi xuebao, 2021)
In order to calculate the minimum inserted depth of rigid anti-slide piles in stable soil with oblique top surface in the downslope area of the piles in a reinforced slope under a specified factor of safety, according to elastic-foundation-coefficient method under oblique top surface of the ground to determine lateral compressive stress on the soil mass surrounding embedded segment of the pile, together with plasticity limit analysis method to compute lateral ultimate bearing capacity related to dip angle of the slip surface in the downslope area of the piles, a computation procedure for the minimum inserted depth is proposed on the basis of the limitation condition that the maximum compressive stress is not more than the ultimate bearing capacity. The relationship between the minimum inserted depth and the dip angle can be determined. Analysis results of a practical example show that the minimum inserted depth of anti-slide piles increases nonlinearly with the dip angle, and changes significantly within the range of 10°～30°; Cohesion, internal friction angle- and unit weight of the stable layer have clear effect on the minimum inserted depth, and there are negative correlations between them. The minimum inserted depth of the pile obtained by the proposed method is about 18% smaller than that obtained by the traditional method considering the oblique condition of the slip surface in the downslope area of the piles.